Phon kānl̄ưaktang samāchik Saphā Rāng Ratthathammanūn nai khant̨̄on kh̨̄ong Ratthasaphā - Niphat Srachanthaphong (ʻĒkkasān wongngān Ratthasaphā, 1997)
Study and report on elections of Constitution Drafting Assembly, Thailand.